G-c3n4 / wo3 quantum dot light / dark continuous catalytic material, preparation method and application thereof

CN122974348APending Publication Date: 2026-10-27XINJIANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611144818.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供g-C3N4/WO3量子点光/暗连续催化材料的制备方法,解决了现有电子存储材料可逆存储位点密度有限,暗态放电容量与持续性不足

Benefits of technology

(1)本发明通过化学自组装法制备二维膨胀且富含氮空位的g-C3N4,结合WO3量子点构建异质结界面,一方面利用氮空位及变价金属中心W5+/6+捕获光生电子、抑制复合,另一方面通过WO3量子点与g-C3N4的能带匹配促进电荷定向迁移,使光生载流子分离效率显著高于现有单相材料;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974348A_ABST
    Figure CN122974348A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material, specifically: through a chemical self-assembly method, graphite phase carbon nitride which is two-dimensional expansion and rich in nitrogen vacancies is obtained after a thermal reaction, and on the basis, WO3 quantum dots under different ultrasonic conditions are sequentially stirred, calcined, cooled and ground, and the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is obtained. Through the synergistic effect of WO3 quantum dots and nitrogen vacancy g-C3N4, the application enhances the response ability of the material to near-infrared light, realizes visible light and near-infrared light synergistic catalysis, and keeps stable catalytic activity in light / dark environment, and solves the defects that the prior art is strongly dependent on light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic wastewater pollutant removal catalyst technology, specifically relating to g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials, a preparation method for g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials, and applications of g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials. Background Technology

[0002] Antidepressants (ATDs), as a key subclass of emerging pollutants (ECs), are experiencing rapid sales growth at an average annual rate of 4.08%. However, the structural contradiction between the overuse of ATDs and the low removal efficiency of traditional treatment processes is exacerbating the environmental pollution problem caused by ATDs. Venlafaxine (VEN), a first-line antidepressant, and its metabolite desmethylvenlafaxine (ODV) have concentrations in wastewater treatment plant influent ranging from 59.5 to 1677.1 ng / L and 520 to 2449.5 ng / L, respectively, significantly higher than other ATDs. Notably, the median concentration of VEN in wastewater treatment plant effluent (166 ng / L) is significantly higher than that in influent (11 ng / L), with an enrichment factor of 15 times, and its apparent removal efficiency exhibits extreme fluctuations ranging from -1343% to 59%. This "negative removal" phenomenon originates from the demethylation reaction in the biological treatment unit, which metabolizes VEN (accounting for 90% of the initial VEN flux), and then re-converts it back into the parent compound VEN through a microbial enzymatic reverse reaction. This metabolic-reconversion process exacerbates the accumulation of VEN in the aquatic ecosystem, thereby inducing community structure imbalance and ecosystem function degradation, posing a hidden threat to human health and aquatic ecological security, and also presenting a more severe challenge to its in-depth treatment.

[0003] Compared to traditional wastewater treatment methods that rely on high-energy consumption, photocatalysis technology overcomes the energy input bottleneck, providing a theoretical possibility for constructing green water treatment systems. Studies have shown that the removal efficiency of VENs by a photocatalytic-biological coupling system can be increased from ~30% to ~85% in a purely biological unit, and the toxicity of the intermediate product (IP) formed after photocatalysis is also lower than that formed during biological processes. This difference indicates that photocatalysis technology has significant advantages in the simultaneous removal and detoxification of antidepressants. Currently, a series of materials, including metal oxides, sulfides, carbon-based catalysts, hydrotalcite, and their composite catalysts, have been proven to efficiently degrade VENs under photoexcitation. In summary, photocatalysis can efficiently remove VENs while simultaneously reducing ecotoxicity, laying a solid theoretical foundation for constructing a sustainable technological route for VEN pollution control.

[0004] Electronic storage materials using variable valence metal oxides via reversible intermediate valence states (M... n+ / M (n+1)+ The capture and release mechanism of photogenerated electrons enables transient storage and is considered a key bridge connecting solar energy conversion with continuous catalysis under light / dark conditions. However, existing electron storage materials, such as variable-valence metal oxides, suffer from high recombination rates and low migration efficiency of photogenerated carriers, leading to severe effective charge loss during the charging phase; limited reversible storage site density results in insufficient dark-state discharge capacity and persistence; and the wide bandgap significantly inhibits their dark-light catalytic activity, failing to meet the requirements for electron storage. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials, which solves the problems of limited reversible storage site density and insufficient dark-state discharge capacity and duration of existing electronic storage materials.

[0006] A second objective of this invention is to provide g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials.

[0007] The third objective of this invention is to provide the application of g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials in the degradation of organic pollutants in wastewater.

[0008] The first technical solution adopted in this invention is a method for preparing g-C3N4 / WO3 quantum dot light / dark continuous catalytic material, specifically: two-dimensional expanded graphitic carbon nitride rich in nitrogen vacancies is obtained after thermal reaction by chemical self-assembly, and then WO3 quantum dots under different ultrasonic conditions are stirred, calcined, cooled and ground in sequence to obtain the material.

[0009] The invention is further characterized by: The precursors in the chemical self-assembly method are phosphoric acid and melamine, with dosages of 0.8 g and 1.0 g, respectively.

[0010] The calcination conditions for the thermal reaction in the chemical self-assembly method are: calcination at 550℃ for 4 hours, and the ultrasonic conditions for the preparation of WO3 quantum dots are: continuous ultrasonication at 25℃ for 5~20 hours.

[0011] The loading ratio of WO3 quantum dots to g-C3N4 is one of 5%, 10%, 30%, and 50%.

[0012] The mixture of WO3 quantum dots and nitrogen-deficient g-C3N4 was sonicated for 1 hour, stirred continuously for 12 hours, and then dried at 60°C.

[0013] The composite calcination conditions for WO3 quantum dots and nitrogen-deficient g-C3N4 were: heating at a rate of 10 °C / min and holding at 300 °C for 1 h.

[0014] The specific steps are as follows: Step 1. Dissolve phosphoric acid and melamine in ultrapure water and stir at pH=2 for 30 min. Transfer the mixture to a high-pressure reactor lined with polytetrafluoroethylene and heat at 180°C for 10 h to obtain a precipitate. Centrifuge the precipitate and wash it 10 times with deionized water. Then dry it at 60°C to obtain the nitrogen defect g-C3N4 sample. Step 2. WO3 was continuously sonicated at 25°C for 5-20 h. The resulting bright yellow solution was filtered through a 0.22 μm filter membrane and dried at 60°C under low pressure to obtain the powdered solid product WO3 quantum dots. Step 3. Sonicate the nitrogen-deficient g-C3N4, add WO3 quantum dots, then sonicate for 1 hour and stir vigorously for 12 hours. Dry the precipitate at 60°C, heat the precipitate at a rate of 10°C / min, and calcine it at 300°C for 1 hour to obtain the final product.

[0015] The second technical solution adopted in this invention is a method for preparing g-C3N4 / WO3 quantum dot light / dark continuous catalytic material.

[0016] The third technical solution adopted in this invention is the application of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material in the degradation of organic pollutants in wastewater.

[0017] The third technical solution adopted in this invention is further characterized by, Organic pollutants include antidepressants, antibiotics, and dyes.

[0018] The beneficial effects of this invention are: (1) This invention prepares two-dimensional expanded g-C3N4 rich in nitrogen vacancies by chemical self-assembly, and constructs a heterojunction interface by combining it with WO3 quantum dots. On the one hand, it utilizes nitrogen vacancies and variable valence metal centers W 5+ / 6+ By capturing photogenerated electrons and suppressing recombination, and by promoting the directional migration of charge through band matching between WO3 quantum dots and g-C3N4, the separation efficiency of photogenerated carriers is significantly higher than that of existing single-phase materials. (2) By regulating the synergistic effect of WO3 quantum dots and nitrogen vacancy g-C3N4, this invention enhances the material’s response to near-infrared light, achieves synergistic catalysis of visible and near-infrared light, maintains stable catalytic activity under light / dark conditions, and solves the problem of strong light dependence in existing technologies.

[0019] (3) The present invention adopts a chemical self-assembly method (hydrothermal reaction + ultrasonic dispersion + calcination), which is simple and mild, and does not require complex equipment or special reagents, thus reducing the preparation cost and energy consumption. Compared with the existing preparation methods that require high temperature and high pressure and multi-step reaction, this method is easier to achieve industrial scale-up and is conducive to promoting the practical application of photocatalysis technology. Attached Figure Description

[0020] Figure 1 This is a flowchart of the preparation process of the present invention; Figure 2 This is a scanned image of the catalytic material obtained in Example 1 of the present invention; Figure 3 This is the XPS image of the catalytic material obtained in Example 1 of this invention; Figure 4 This is a diagram showing the photocatalytic degradation of VEN by the catalytic material of this invention; Figure 5 This is a diagram showing the light / dark cycle catalytic degradation of VEN by the catalytic material of this invention; Figure 6 These are the free radical capture experimental results and EPR characterization diagram of the catalytic material obtained in Example 1 of this invention; Figure 7 This is a graph showing the degradation efficiency of VEN by the g-C3N4 / WO3 quantum dot photocatalytic system obtained in Example 1 of this invention; Figure 8 This describes the effect of the g-C3N4 / WO3 quantum dot system obtained in Example 1 of this invention on VEN degradation; Figure 9 This is an electrochemical characterization diagram of the g-C3N4 / WO3 quantum dot system obtained in Example 1 of this invention; Figure 10The results show the photocatalytic coefficient and VEN degradation efficiency of the g-C3N4 / WO3 quantum dot system obtained in Example 1 of this invention after 5 cycles. Figure 11 This is a flowchart illustrating the engineering application of the g-C3N4 / WO3 quantum dot catalyst for photocatalytic removal of VENs obtained in Example 1 of this invention. Detailed Implementation

[0021] The following detailed description is provided in conjunction with specific implementation methods and accompanying drawings.

[0022] The present invention discloses a method for preparing g-C3N4 / WO3 quantum dot light / dark continuous catalytic materials, which specifically involves obtaining two-dimensional expanded graphitic carbon nitride (g-C3N4) rich in nitrogen vacancies through a chemical self-assembly method after a thermal reaction, and then sequentially stirring, calcining, cooling, and grinding WO3 quantum dots under different ultrasonic conditions to obtain the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material.

[0023] The graphite phase g-C3N4 precursors are phosphoric acid (H3PO4) and melamine (C3H6N6), with dosages of 0.8 g and 1.0 g, respectively.

[0024] The calcination conditions for the thermal reaction in the chemical self-assembly method are: calcination at 550℃ for 4 hours, and the ultrasonic conditions for the preparation of WO3 quantum dots are: continuous ultrasonication at 25℃ for 5~20 hours.

[0025] The ratio of WO3 quantum dots to g-C3N4 is one of 5%, 10%, 30%, and 50%.

[0026] The mixture of WO3 quantum dots and nitrogen-deficient g-C3N4 was sonicated for 1 hour, stirred continuously for 12 hours, and then dried at 60°C.

[0027] The composite calcination conditions for WO3 quantum dots and nitrogen-deficient g-C3N4 were: heating at a rate of 10 °C / min and holding at 300 °C for 1 h.

[0028] Due to the excellent stability, high redox properties, tunable electronic structure, and good conductivity of nitrogen-deficient g-C3N4, the introduction of N vacancies and the presence of melamine functional groups can induce strong e-elements. - Accumulation and new e -Storage properties are utilized to effectively promote photogenerated carrier separation. Starting from the structural extension and nitrogen vacancies of g-C3N4 material itself, while ensuring effective two-dimensional planar expansion, a large number of nitrogen defects are retained to regulate the light absorption range of the material in the near-infrared region. This provides a continuous and sufficient supply of photogenerated electrons for WO3 quantum dots as electronic storage materials. Furthermore, a fast charge transfer channel is constructed through a tight point contact interface with WO3 quantum dots, synergistically enhancing the electron storage capacity and dark-state release efficiency of the system under broad-spectrum excitation, as well as the sustainable dark-light catalytic ability of the g-C3N4 / WO3 quantum dot system in dark environments. Based on this, by systematically controlling the quantum dot size and gradient nitrogen vacancy concentration, the energy level structure, interfacial charge transfer barrier, and surface reactivity of the composite material are further optimized. The goal is to improve its sustainable degradation efficiency of trace antidepressant drugs VEN under alternating light and dark conditions and to further reveal its photochemical properties. The dark synergistic catalytic pathway and electron migration patterns provide a theoretical basis for developing new deep purification technologies for pollutants that are adapted to intermittent solar energy input.

[0029] Furthermore, since the selected phosphoric acid (H3PO4) and melamine (C3H6N6) are soluble in ultrapure water, this not only reduces the synthesis cost but also minimizes the environmental pollution caused by organic solvents, thus contributing to the synthesis of green and environmentally friendly target catalysts. Moreover, different calcination temperatures and times are defined during the catalyst synthesis process of this invention. These conditions significantly affect the crystal structure, specific surface area, and photocatalytic performance of the catalyst. By optimizing these conditions, the physicochemical properties of the catalyst can be controlled, thereby enhancing its catalytic activity.

[0030] This invention uses phosphoric acid (H3PO4) and melamine (C3H6N6) as precursors to obtain two-dimensional expanded graphitic carbon nitride (g-C3N4) rich in nitrogen vacancies through a chemical self-assembly method. Based on this, WO3 quantum dots under different ultrasonic conditions are sequentially stirred, calcined, cooled, and ground to successfully prepare a g-C3N4 / WO3 quantum dot all-weather photocatalyst. The chemical self-assembly method involves controlling the thermal reaction temperature (e.g., continuous calcination at 550℃ for 10 h) to form a two-dimensional expanded structure of g-C3N4 and introduce nitrogen vacancies. Simultaneously, ultrasonication optimizes the size of the WO3 quantum dots and ensures their uniform dispersion on the g-C3N4 surface. Starting from the structural expansion and nitrogen vacancies of g-C3N4 material itself, this method ensures effective expansion of the two-dimensional plane while retaining a large number of nitrogen defects to regulate the light absorption range of the material. This provides a continuous and sufficient supply of photogenerated electrons for WO3 quantum dots, which serve as electron storage materials. Furthermore, a rapid charge transfer channel is constructed through a tight point contact interface with WO3 quantum dots, synergistically enhancing the electron storage capacity and dark-state release efficiency of the system under broad-spectrum excitation. This synergistic effect enhances the photocatalytic degradation performance of the photocatalytic material under light response, providing a highly efficient, all-weather photocatalytic material for degrading organic pollutants in wastewater (such as antidepressants, antibiotics, and dyes).

[0031] The g-C3N4 / WO3 quantum dot photo / dark continuous catalytic material prepared by the method generates photogenerated electron-hole pairs under photoresponse, which can oxidize and degrade organic pollutants in wastewater.

[0032] Organic pollutants include antidepressants (venlafaxine (VEN) and amitriptyline (AMT)), antibiotics (tetracycline (TC) and fluoroquinolones (FLX)) and dyes (methyl orange (MO) and methyl red (MR)).

[0033] Example 1 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. A 10% loading of WO3 quantum dots (sonicated for 20 h) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-10.

[0034] Example 2 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The mixture was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. WO3 quantum dots with a loading of 5% (sonicated for 20 h) were dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-5.

[0035] Example 3 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. WO3 quantum dots with a loading of 30% (sonicated for 20 h) were dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-30.

[0036] Example 4 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. WO3 quantum dots with a loading of 50% (sonicated for 20 h) were dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-50.

[0037] Example 5 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. WO3 quantum dots with a loading of 50% (sonicated for 5 h) were dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-50.

[0038] Example 6 The preparation method of g-C3N4 / WO3 quantum dot light / dark continuous catalytic material is carried out according to the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and then sonicated for 30 min to obtain solution 1. A 10% loading of WO3 quantum dots (sonicated for 5 h) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3 quantum dots-10.

[0039] Comparative Example 1 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene and heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions to obtain g-C3N4.

[0040] Comparative Example 2 WO3 was dispersed in an ethanol solution and then subjected to continuous ultrasonic treatment for 20 h to obtain WO3 quantum dots.

[0041] Comparative Example 3 A method for preparing a g-C3N4 / WO3 photocatalyst includes the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and sonicated for 30 min to obtain solution 1. A 5% loading of WO3 (unsonicated) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3-5.

[0042] Comparative Example 4 A method for preparing a g-C3N4 / WO3 photocatalyst includes the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and sonicated for 30 min to obtain solution 1. A 10% loading of WO3 (unsonicated) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3-10.

[0043] Comparative Example 5 A method for preparing a g-C3N4 / WO3 photocatalyst includes the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The mixture was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and sonicated for 30 min to obtain solution 1. 30% WO3 (unsonicated) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3-30.

[0044] Comparative Example 6 A method for preparing a g-C3N4 / WO3 photocatalyst includes the following steps: 0.80 g of phosphoric acid (H3PO4) and 1.00 g of melamine (C3H6N6) were dissolved in 100.00 mL of deionized water and stirred for 30 min (pH=2). The solution was transferred to an autoclave lined with polytetrafluoroethylene (PTFE) with a filling factor of 0.75. The solution was heated at 180 °C for 10 h to obtain a precipitate. The precipitate was centrifuged and washed 10 times with deionized water. After drying at 60 °C, the sample was heat-treated at 550 °C under anaerobic conditions and sonicated for 30 min to obtain solution 1. 50% WO3 (unsonicated) was dispersed in solution 1, followed by sonication for 1 h and vigorous stirring for 12 h, and then dried at 60 °C. The resulting precipitate was placed in an open alumina crucible, heated at a rate of 10 °C / min, and held at 300 °C for 1 h to obtain g-C3N4 / WO3-50.

[0045] Effect verification 1. Characterization Test like Figure 1 The diagram shows the preparation process of this invention. g-C3N4 and g-C3N4 / WO3 quantum dot composites were synthesized via a hydrothermal-calcination method. As can be seen from the diagram, g-C3N4 was prepared by hydrothermal-calcination using melamine and phosphoric acid as precursors. WO3 quantum dots were then prepared by ultrasonication. Subsequently, g-C3N4 and WO3 quantum dots were combined to obtain g-C3N4 / WO3 quantum dots. This composite material has a tight point contact interface, and its energy level structure can be tuned to improve the electron storage capacity and dark-state release efficiency under broad-spectrum excitation, thereby enhancing the sustainable degradation ability of trace antidepressant drugs VEN under alternating light and dark conditions.

[0046] Figure 2 The images shown are scanning electron microscope (SEM) images of the catalyst obtained in Example 1 of this invention; where ab are SEM images of nitrogen-deficient g-C3N4 at different magnifications; ce are TEM images of WO3 quantum dots and their corresponding particle size distribution; fi are TEM images of g-C3N4 / WO3 quantum dots; jk are corresponding EDS images of g-C3N4 / WO3 quantum dots; it can be seen that the catalyst obtained in Example 1 exhibits a microstructure of uniformly dispersed particles on a rod-shaped structure, and the elements are uniformly distributed.

[0047] Figure 3 The above are XPS images of the catalyst obtained in Example 1 of this invention; where ad are the C 1s, N 1s, O 1s and W 4f XPS spectra of the g-C3N4 / WO3 quantum dot catalyst before and after the photocatalytic reaction, respectively; ef are the O 1s and W 4f spectra of WO3 quantum dots at different ultrasonic times, respectively; gh are the XPS images of nitrogen-deficient g-C3N4, WO3 quantum dots and g-C3N4 / WO3 quantum dots, respectively. In this invention, SEM, TEM, and EDS analyses confirmed the successful preparation of the g-C3N4 / WO3 quantum dot photocatalyst. The three-dimensional rod-like structure, large specific surface area, and high mechanical strength of g-C3N4 provided an excellent environment for the uniform dispersion of WO3 quantum dots. XPS full-spectrum analysis confirmed the presence of C, N, O, and W elements in the g-C3N4 / WO3 quantum dot photocatalyst material. Comparison of the full-spectrum images of the catalyst before and after the cyclic reaction showed that the peak positions did not change and no additional peaks were formed, demonstrating the significant stability of the catalyst.

[0048] 2. Degradation experiment This experiment used VEN (20 mg / L) as the target pollutant and conducted a room temperature degradation experiment in 50 mL of solution to simulate antidepressant drug pollution in the environment. The photocatalyst sample was immersed in simulated VEN wastewater (gradient concentration) and stirred continuously for 30 min to reach adsorption equilibrium. Subsequently, photocatalytic degradation was carried out under 300 W xenon lamp irradiation. At set time intervals, 2 mL of the treated water sample was filtered through a 0.45 μm membrane. The residual concentration of VEN was detected by high-performance liquid chromatography (HPLC) using an Agilent HC-C18 column (5 μm, 250 mm × 4.6 mm). The sample injection volume and mobile phase flow rate were 20 μL and 1 mL / min, respectively. The mobile phase ratio was 0.05 M phosphoric acidified disodium hydrogen phosphate and acetonitrile (v / v = 64 / 36). The detection wavelength was 226 nm. After the reaction was completed, the catalyst was recovered, washed 2-3 times with deionized water and anhydrous ethanol, dried in an oven overnight (60°C, 12 h), and collected for reuse experiments. All experiments were performed at least two to three times, and average data and their error values ​​are given.

[0049] Figure 4 In Figure a, g-C3N4, WO3 quantum dots, and g-C3N4 / WO3 quantum dots (corresponding to Example 1 and Comparative Examples 1-2) affect the photocatalytic degradation efficiency of VEN. Figure b shows the effects of different catalyst synthesis categories (corresponding to Examples 1-4 (g-C3N4 / WO3 quantum dots) and Comparative Examples 3-6 (g-C3N4 / WO3)) on the photocatalytic degradation efficiency and degradation rate constant of VEN. The optimal photocatalytic degradation effect of VEN is achieved when the loading rate of WO3 quantum dots in the g-C3N4 / WO3 quantum dot composite photocatalytic material is 10%.

[0050] Figure 5 In Figure a, g-C3N4, WO3 quantum dots, and g-C3N4 / WO3 quantum dots (corresponding to Example 1 and Comparative Examples 1-2) are shown to have different reaction times on the continuous light / dark catalytic degradation efficiency of VEN. Figure b shows the continuous light / dark catalytic degradation efficiency and degradation rate constant of VEN for different catalyst synthesis categories (corresponding to Examples 1-4 (g-C3N4 / WO3 quantum dots) and Comparative Examples 3-6 (g-C3N4 / WO3)). The optimal continuous light / dark catalytic degradation effect on VEN is achieved when the loading rate of WO3 quantum dots in the g-C3N4 / WO3 quantum dot composite photocatalyst is 10%. The core reason lies in the effect of loading rate on the structure-performance balance. The synergistic storage of photogenerated electrons by nitrogen vacancies and variable valence metal centers significantly improves the photocatalytic and continuous light / dark catalytic performance of the composite photocatalyst for VEN.

[0051] 3. Assay for bioactive species The experimental steps for free radical capture are as follows: To confirm and quantify the reactive species (ROS) generated during the photocatalytic degradation reaction of the photocatalyst system of this invention, free radical quenching experiments were conducted using methanol (MeOH), tert-butanol (TBA), p-benzoquinone (p-BQ), and L-histidine as ROS scavengers. The quenchers were added before the catalyst and light response, i.e., before the initiation of the photocatalytic and light / dark sequential catalytic degradation reactions. This experiment also employed a single-factor controlled variable method and was compared with a blank experiment without quenchers.

[0052] The experimental procedure for EPR electron paramagnetic resonance is as follows: Electron paramagnetic resonance (EPR) spectroscopy was used to further verify the presence of ROS in the reaction system. 5,5-Dimethyl-1-pyrrolline-N-oxide (DMPO) was used as SO4. - 4-Amino-2,2,6,6-Tetramethylpiperidine (TEMP) is used as a spin trapping agent for OH·. 1 O2 spin trapping agent. The preparatory procedures before the test are as follows: First, replace the target pollutant with an equal volume of deionized water, then add a certain amount of catalyst and turn on the xenon lamp to start the experiment. At the set time point, take out a certain volume of the reaction solution and mix it with the spin trapping agent. Use a clean capillary tube to draw up the above mixture, and finally, place it at the bottom of a narrow-mouthed quartz tube to begin the test.

[0053] Figure 6 The free radical capture experiment results (ae) and electron paramagnetic resonance (EPR) characterization spectrum (fi) of the catalyst prepared in Example 1 of this invention are shown. The free radical capture experiment involved adding different quenchers (such as p-benzoquinone (p-BQ), used to quench superoxide radicals·O2). - Isopropanol (IPA, used to quench hydroxyl radicals OH·), and ethylenediaminetetraacetic acid (EDTA, used to quench photogenerated holes h·) + ), benzoquinone (BQ, used to quench photogenerated electrons e), - The contribution of each bioactive species to VEN degradation was investigated; EPR characterization was performed using DMPO (used to capture OH· and O2·). - ) and TEMP (used to capture singlet oxygen) 1 O2) spin trapping agent was used, and signal intensity was recorded under different conditions. From the results of quenching experiments and EPR analysis, it can be clearly inferred that photogenerated electrons (electrons) exist in the g-C3N4 / WO3 quantum dot photocatalytic system. - ), photogenerated holes (h) + ), hydroxyl radicals (OH·), superoxide radicals (·O2) - ) and singlet oxygen ( 1O2). Among them, photogenerated electrons and holes serve as initial active centers and can participate in reduction and oxidation reactions, respectively; OH·, ·O2 - and 1 O2, acting as a strong oxidizing free radical, degrades VEN by attacking specific functional groups (such as benzene rings and amino groups) in the VEN molecule. Synergistic verification through free radical capture experiments and EPR characterization clarifies that the degradation process of VEN by this system is driven by free radicals (OH·, O2·). - and 1 O2) and non-free radicals (e) - h + This is the result of the synergistic effect of the redox pathway (mediated by oxidation-reduction reaction). This multi-pathway synergistic mechanism not only improves degradation efficiency but also enhances the stability of the system.

[0054] 4. Stability and anti-interference test Cyclic test procedure: After each reaction, the catalyst is removed from the reaction solution, washed 2-3 times with deionized water and anhydrous ethanol, dried in an oven overnight (60℃, 12 h), and collected for reuse tests.

[0055] Figure 10 a represents the photocatalytic coefficient of the g-C3N4 / WO3 quantum dot catalyst obtained in Example 1 of this invention, based on the results of cyclic experiments on the g-C3N4 / WO3 quantum dot system before and after use of the photocatalytic material. Figure 10 As can be seen from Figure b, the catalyst obtained in Example 1 of this invention still maintains a degradation efficiency of over 100% after 5 cycles, demonstrating excellent reusability and stability. The synergistic effect of g-C3N4 / WO3 quantum dots in this reaction effectively maintains the stability of the photocatalytic material while preserving the catalytic activity of the photocatalyst, and also improves the stability and reusability of the composite material.

[0056] Figure 7 The effects of the g-C3N4 / WO3 quantum dot photocatalytic system obtained in Example 1 of this invention on VEN degradation under different photocatalyst dosages (a), the effects of different concentrations on VEN degradation efficiency (b), VEN degradation efficiency under different pH conditions (c), VEN degradation efficiency (df) under different cation interference environments, and VEN degradation efficiency (gi) under different anion interference environments are shown. Figure 8 The effects of the g-C3N4 / WO3 quantum dot photocatalytic system obtained in Example 1 of this invention on the degradation efficiency of different pollutants (a) and the COD removal performance of VEN (b) are shown. Figure 7 and Figure 8 As can be seen, the degradation effect of VEN is almost unaffected by different concentrations and cation and anion interference environments, indicating that the system has good practical applicability.

[0057] 5. Electrochemical testing The generation, transformation, and degradation pathway of VEN degradation products in the g-C3N4 / WO3 quantum dot photocatalytic system were explained using liquid chromatography-mass spectrometry (LC-MS) analysis. The specific steps are as follows: The intermediates of VEN in the catalytic reaction system were analyzed using a Thermo Fisher UItiMate 3000 high-performance liquid chromatography-mass spectrometry (HPLC-MS). The instrument settings were as follows: mobile phase consisted of methanol (A) and water (B); the gradient started at 10% A and continued for 2 min, then linearly increased to 40% A over 18 min, then linearly increased to 90% A over 20 min, and then returned to the initial conditions over 5 min, maintaining equilibrium for 5 min. The chromatographic column was C18, the detection wavelength was 278 nm, the injection volume was 80 μL, and the flow rate was 0.6 mL / min.

[0058] The results are shown in Table 1. Table 1 shows the VEN intermediates identified by HPLC-MS / MS in the g-C3N4 / WO3 quantum dot photocatalytic system.

[0059] Table 1

[0060] Continued table

[0061] Continued table

[0062] As can be seen from Table 1, VEN degradation produces many ring-opening products, which are easily oxidized to produce carbon dioxide and water.

[0063] Figure 7 In Example 1 of this invention, a represents the effect of the g-C3N4 / WO3 quantum dot catalytic system on the VEN degradation efficiency under different dosage conditions; b represents the degradation efficiency of VEN at different concentrations; c represents the VEN degradation efficiency under different pH conditions; df represents the VEN degradation rate under different cation interferences; and gi represents the VEN degradation efficiency under different anion interferences. Figure 8This diagram shows the degradation efficiency of various novel pollutants by the g-C3N4 / WO3 quantum dot photocatalytic system obtained in Example 1 of this invention, evaluating the versatility, anti-interference capabilities, and environmental adaptability of the catalytic system. This invention targets emerging pollutants such as antidepressants (venlafaxine (VEN) and amitriptyline (AMT)), antibiotics (tetracyclines (TC) and fluoroquinolones (FLX)), and dyes (methyl orange (MO) and methyl red (MR)), examining the relationship between the structure of different pollutants and their removal rates. It can be seen that the presence of substituents in pollutants generally affects removal efficiency, as some reactive oxygen species are more likely to attack certain specific structures or groups on the pollutants. From... Figure 8 As shown in (a), the g-C3N4 / WO3 quantum dot photocatalytic system exhibits significant removal efficiency for pollutants such as venlafaxine (VEN), amitriptyline (AMT), tetracycline (TC), methyl orange (MO), and methyl red (MR), with removal efficiencies exceeding 75% within 60 min; however, the removal efficiency for fluoroquinolones (FLX) is only 50.0%. This difference is mainly due to the differences in the molecular structure of the pollutants: antidepressants containing amino groups and large aromatic rings, such as VEN and AMT, are easily oxidized by OH· or h· + Direct oxidation; the amino, hydroxyl, and conjugated double bond functional groups in VEN, AMT, TC, MO, and MR molecules readily react with photogenerated free radicals (such as OH·, ·O2). - and 1 O2) undergoes an oxidation reaction, and these contaminants have a strong adsorption capacity on the catalyst surface, which is conducive to the reaction. TC antibiotics containing phenolic hydroxyl groups and conjugated double bonds can pass through O2. - Attack unsaturated bonds, 1 O2 oxidation of phenolic hydroxyl groups is effectively degraded; MO and MR dyes containing azo bonds (-N=N-) can be degraded via h + The azo bonds are directly broken, and the conjugated structure is oxidized and removed through ·OH oxidation. The high electronegativity of fluorine atoms in the FLX molecule may enhance its chemical stability, or its molecular size and steric hindrance may lead to lower contact efficiency with the catalyst's active sites. Simultaneously, the hydrophilicity of FLX or its weak interfacial interaction with the catalyst makes it difficult for photogenerated charge carriers to be effectively transferred to the FLX molecule, thus reducing the degradation efficiency. These results indicate that the g-C3N4 / WO3 quantum dot photocatalytic system exhibits selective oxidation of different organic pollutants.

[0064] 6. Electrochemical testing To further investigate the charge transfer mechanism and interfacial electronic dynamics in the g-C3N4 / WO3 quantum dot photocatalytic system, electrochemical performance characterization was carried out using linear sweep voltammetry (CV), polarization curves and chronoamperometry (it curves), and open-circuit potential.

[0065] All tests were performed in a standard three-electrode system, with a conductive substrate loaded with the target catalyst as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode (to ensure the accuracy of potential measurements). The electrolyte buffer was a 0.05 mol / L saturated Na2SO4 solution, which provides a stable ionic environment to ensure the smooth progress of the electrochemical reaction.

[0066] Figure 9 The images show the electrochemical characterization of the g-C3N4 / WO3 quantum dot photocatalytic material obtained in Example 1 of this invention. To determine the electron transfer mechanism in the g-C3N4 / WO3 quantum dot photocatalytic system, the electrochemical performance of the reaction system under different conditions was tested. (a) is the linear sweep voltammetry (CV), (b) is the polarization curve, (c) is the chronoamperometry (it curve), and (d) is the open-circuit potential. Figure 9 As shown in Figure (a), at the same potential, the current density is lowest when VEN is added to the electrolyte with a conductive substrate loaded with g-C3N4 / WO3 quantum dot photocatalyst as the working electrode in a dark environment. The current density is highest after 1 h of pre-illumination. The current density decreases sequentially after 0.5 h, 1 h, 2 h, and 3 h of illumination followed by light-off. This indicates that the electrons stored in the g-C3N4 / WO3 quantum dot photocatalytic system during illumination are gradually released as the light-off time increases, and the release rate gradually slows down over time. This reflects the excellent electron storage and slow-release capacity of the system, which allows the photocatalytic reaction to continue in the dark, thus explaining the system's high-efficiency degradation performance of pollutants such as VEN under alternating light / dark conditions. Figure 9As shown in (b), under dark conditions, the g-C3N4 / WO3 quantum dot photocatalyst cannot absorb photons to generate photogenerated electron-hole pairs. The number of electrons available for electrochemical reactions in the system is extremely small, resulting in the lowest current density. Under illumination, g-C3N4 absorbs photons to generate photogenerated electrons and holes. Due to the more negative conduction band potential of WO3 quantum dots and the more positive conduction band potential of g-C3N4, photogenerated electrons transfer from g-C3N4 to WO3 quantum dots and are stored (WO3 quantum dots act as an electron storage layer), while holes remain on the surface of WO3 quantum dots. This directional transfer and storage of electrons increases the electron concentration on the electrode surface, thus significantly increasing the current density compared to dark conditions. Pre-irradiation refers to storing electrons in the system under illumination before conducting the illumination test. In this case, the system not only generates new photogenerated electrons but also releases electrons stored during pre-irradiation. This dual electron source causes the current density to reach its peak, demonstrating the synergistic effect of electron storage and photoexcitation. After pre-irradiation, the electrons stored in g-C3N4 are slowly released in the dark (transferred to WO3 quantum dots through the heterojunction interface to participate in the reaction), resulting in a higher current density than under dark conditions without pre-irradiation. As the light-off time increases (0.5 h → 3 h), the stored electrons are gradually depleted, and the current density decreases sequentially, which directly reflects the system's electron slow-release capability, i.e., it can still utilize stored electrons to degrade pollutants in the dark. Figure 9 (c) shows the transient photocurrent (it) curve, which tests the current response of the g-C3N4 / WO3 quantum dot photocatalytic system under light-dark switching. Under light, the g-C3N4 / WO3 quantum dots generate photogenerated electron-hole pairs and store electrons under photoexcitation, causing the current density to increase; under darkness, the stored electrons are slowly released, and the current decreases. The longer the pre-irradiation time (1h, 2h), the more electrons g-C3N4 stores, the higher the current under light, and the slower the current decreases after darkness. The difference in the curves indicates that the system achieves continuous light / dark catalysis through electron storage and slow release, verifying the charge separation and storage capabilities of the heterojunction. Figure 9(d) shows the curve of open circuit potential (OCP) versus time. The vertical axis represents potential (V vs Ag / AgCl), and the horizontal axis represents time (s). The three curves correspond to the materials g-C3N4, WO3 quantum dots, and g-C3N4 / WO3 quantum dots, respectively. The curves show that the potential of all three decreases with time, indicating that the materials undergo redox reactions in the electrolyte, leading to a gradual decrease in potential. The order of potential from highest to lowest is g-C3N4 > g-C3N4 / WO3 quantum dots > WO3 quantum dots. This is because g-C3N4 has a higher redox potential and stronger oxidizing ability; WO3 quantum dots have a lower potential; and the g-C3N4 / WO3 quantum dot composite material, due to the formation of a heterojunction and optimized band structure, has a potential between the two. The decrease in potential over time may be due to the reaction between the material surface and ions in the electrolyte, consuming active species or accumulating charge, leading to a gradual decrease in potential. This result reflects the redox characteristics of different materials and the regulatory effect of composite materials on the band structure.

[0067] The above electrochemical tests further demonstrate that the g-C3N4 / WO3 quantum dot catalyst has excellent electron transfer and storage capabilities, promotes the generation of free radicals and non-free radical pathways, and thus achieves better degradation results.

[0068] 7. Engineering application process and mechanism of g-C3N4 / WO3 quantum dot photocatalytic system Figure 11 This is a flowchart illustrating the engineering application of the g-C3N4 / WO3 quantum dot photocatalytic material obtained in Example 1 for removing pollutants such as the antidepressant VEN.

[0069] The purification effect of the g-C3N4 / WO3 quantum dot photocatalytic system on mixed wastewater containing VEN (a simulated antidepressant drug) at different influent flow rates (0.2, 0.4, and 0.8 mL / min) was investigated. During 12 hours of continuous operation, the removal of VEN by the g-C3N4 / WO3 quantum dot photocatalytic system at the three flow rates was verified, confirming that the g-C3N4 / WO3 quantum dot photocatalytic system can effectively and continuously remove VEN from wastewater containing simulated antidepressant drugs, thereby reducing its pollution to water bodies.

Claims

1. A method for preparing g-C3N4 / WO3 quantum dot light / dark continuous catalytic material, characterized in that, Specifically, carbon nitride in the graphitic phase, which is two-dimensionally expanded and rich in nitrogen vacancies, is obtained through a chemical self-assembly method after a thermal reaction. Then, it is stirred, calcined, cooled, and ground with WO3 quantum dots under different ultrasonic conditions to obtain the final product.

2. The preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The precursors in the chemical self-assembly method are phosphoric acid and melamine, with dosages of 0.8g and 1.0g, respectively.

3. The preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The calcination conditions for the thermal reaction in the chemical self-assembly method are: calcination at 550℃ for 4 hours, and the ultrasonic conditions for the preparation of WO3 quantum dots are: continuous ultrasonication at 25℃ for 5~20 hours.

4. The preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The loading ratio of WO3 quantum dots to g-C3N4 is one of 5%, 10%, 30%, and 50%.

5. The preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The mixture of WO3 quantum dots and nitrogen-deficient g-C3N4 was sonicated for 1 hour, stirred continuously for 12 hours, and then dried at 60°C.

6. The preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The composite calcination conditions for the WO3 quantum dots and nitrogen-deficient g-C3N4 are: heating at a rate of 10 °C / min and holding at 300 °C for 1 h.

7. The method for preparing the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 1, characterized in that, The specific steps are as follows: Step 1. Dissolve phosphoric acid and melamine in ultrapure water and stir at pH=2 for 30 min. Transfer the mixture to a high-pressure reactor lined with polytetrafluoroethylene and heat at 180°C for 10 h to obtain a precipitate. Centrifuge the precipitate and wash it 10 times with deionized water. Then dry it at 60°C to obtain the nitrogen defect g-C3N4 sample. Step 2. WO3 was continuously sonicated at 25°C for 5-20 h. The resulting bright yellow solution was filtered through a 0.22 μm filter membrane and dried at 60°C under low pressure to obtain the powdered solid product WO3 quantum dots. Step 3. Sonicate the nitrogen-deficient g-C3N4, add WO3 quantum dots, then sonicate for 1 hour and stir vigorously for 12 hours. Dry the precipitate at 60°C, heat the precipitate at a rate of 10°C / min, and calcine it at 300°C for 1 hour to obtain the final product.

8. The g-C3N4 / WO3 quantum dot light / dark continuous catalytic material prepared by the preparation method of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to any one of claims 1-7.

9. The application of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to any one of claims 1-8 in the degradation of organic pollutants in wastewater.

10. The application of the g-C3N4 / WO3 quantum dot light / dark continuous catalytic material according to claim 9 in the degradation of organic pollutants in wastewater, characterized in that, The organic pollutants include antidepressants, antibiotics, and dyes.